Selection Criteria for Library Automation Software - Malwad, N.M. (DESIDOC Journal of Library & Information Technology, 2002)
Readymade software packages are available in the market for a wide range of applications including library housekeeping operations, and information storage and retrieval. Their capabilities differ, prices vary and their versions keep on changing. Selection of suitable software package is an important factor in library automation systems. There are not many publications or case studies discussing the criteria for selecting suitable software. The selection is based on specific needs of the institution, its environment, budget, users, aims and objectives. The paper reviews some selected evaluation works, studies and reports. Various criteria which emerge from these reviews are discussed. http://dx.doi.org/10.14429/dbit.15.2.3179